Effect Of Coated Expanded Polystyrene (Ceps) Beads Aggregates On The Properties Of Hollow Concrete Block - Yazid, Nurulfatin Aqilah Mohd (Universiti Sains Malaysia, 2019)
The construction industry is prospering and expected to continue growing and expected to dominate the overall world economy. Indeed, the construction materials demand will increase undoubtedly. Due to the increasing demand of the resources, brand new innovation or alternatives is needed to overcome the high demand of the construction activities in the future. Therefore the usage of natural materials for construction materials no longer relevant and renewable or waste materials such as polystyrene should be chosen as an alternative. Polystyrene is a versatile plastic materials that is widely used for variety of applications around the world. However, this materials is non bio-degradable so it needs to be recycled in order to have sustainable environment. Polystyrene is advantageous to be used as an alternative in construction industry because of their thermal and sound insulation properties and also their lightweight characteristic. In this study, coated expanded polystyrene (EPS) have been used as partial replacement of fine aggregates in the hollow concrete block. The coating of the EPS help to increase the bond between cement paste and EPS. The hollow concrete block samples are prepared with dry mortar mixture with hydraulic compression machine. Several tests incudes compressive strength, water absorption, density, and initial rate of suction have been conducted to know their properties. Comparison of the properties of samples with and without CEPS have been made. CEPS block samples show less density, more water absorption and lower strength compared to the conventional block samples. Therefore, CEPS block are suitable to be used for lightweight construction and non-load bearing application. If they were to be used as load bearing unit, admixtures and different mix design need to be used to achieve better properties.